Boatowner's mechanical and electrical manual : how to maintain, repair, and improve your boat's essential systems - Calder, Nigel (International Marine / McGraw-Hill, 2005)
If it's on a boat and it has screws, wires, or moving parts, it's covered in Boatowner's Mechanical and Electrical Manual. When you leave the dock with this book aboard, you have at your fingertips the best and most comprehensive advice.